Reaction of Indole Carboxylic Acid/Amide with Propargyl Alcohols: [4+3]-Annulation, Unexpected 3-to 2-Carboxylate/Amide Migration, and Decarboxylative Cyclization - Selvaraj, Karuppu; Debnath, Shubham; Swamy, K. C. Kumara (Organic letters, 2019)
1-Methylindole-3-carboxamides react with substituted propargyl alcohols to afford lactams by [4 + 3]-annulation and carboxamide group migration to the indole-2-position. In contrast, indole-2-carboxylic acids/amides form fused seven membered lactones/lactams (oxepinoindolones/azepinoindolones) upon treatment with substituted propargyl alcohols using catalytic Cu(OTf)(2). Decarboxylative cyclization of 1-methylindole-2- or indole-3-carboxylic acids with substituted propargyl alcohols under Lewis (for 1-methylindole-2-carboxylic acid) or Bronsted (for 1-methylindole-3-carboxylic acid) acid catalysis gives the same 3,4-dihydrocyclopentaindoles, demonstrating 3- to 2-carboxylate migration in the latter case.